Two pioneers of epigenetics: their different paths to chromatin research and DNA methylation, and general reflections on epigenetics - Deichmann, Ute (Frontiers in Epigenetics and Epigenomics, 2024)
The concept of chromatin as a complex of DNA (nuclein at the time) and proteins in the nucleus of eukaryotic cells was generated in the late 19th century. Since the late 20th century, research on DNA methylation that originated in the 1970s and chromatin research have also been labelled epigenetics, a term that originated in developmental biology in the 1940s. Epigenetics now comprises many different research strands related to the regulation of gene activity, such as chemical modifications of histones and DNA, chromatin organization, genome architecture, different types of RNA molecules, and others. To show the various paths on which epigenetic research has developed, I present research and reflections of two pioneers of what later became called epigenetics, Gary Felsenfeld and Adrian Bird. They began their scientific career in very different scientific contexts with both of them crucially contributing to the development of modern chromatin research and the understanding of DNA methylation, respectively. The article is based on authorized transcripts of interviews that I conducted with these researchers, focusing on those parts that are related to chromatin research and epigenetics as well as general reflections on epigenetics and biology.